2021
DOI: 10.1155/2021/6707464
|View full text |Cite
|
Sign up to set email alerts
|

Potential Functions of the BMP Family in Bone, Obesity, and Glucose Metabolism

Abstract: Characteristic bone metabolism was observed in obesity and diabetes with controversial conclusions. Type 2 diabetes (T2DM) and obesity may manifest increased bone mineral density. Also, obesity is more easily to occur in T2DM. Therefore, we infer that some factors may be linked to bone and obesity as well as glucose metabolism, which regulate all of them. Bone morphogenetic proteins (BMPs), belonging to the transforming growth factor- (TGF-) beta superfamily, regulate a diverse array of cellular functions duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…The results showed that the signaling pathways related to cell adhesion, proliferation, and differentiation, such as JAK-STAT and Rap1 signaling pathways, were significantly activated, strongly supporting the idea that OIS plays a regulatory role on the viability and function of BMSCs. Meanwhile, mineralization and osteogenic differentiation-related genes (such as FGF1 , FGF23 , and BMP6 ) as well as their corresponding signaling pathways (such as MAPK and cytokine–cytokine receptor interaction) were significantly upregulated. Furthermore, angiogenesis-related genes (such as VEGFR1 and WNT5A ) as well as their corresponding signaling pathways (such as HIF-1) were significantly upregulated, which might be attributed to the addition of magnesium phosphate, zinc phosphate, and calcium silicate. In addition, ECM restructuring-related pathways (such as osteoclast differentiation) were also significantly activated, suggesting that OIS could regulate the structural remodeling of the regenerated bone. Although further experiments are required for in-depth confirmation, the results of this study imply that the regulatory roles of OIS on bone regeneration result from the synergistic action of various factors, including enhancing adhesion, proliferation, and differentiation, promoting mineralization and angiogenesis, and remodeling the ECM structure, which provided reasonable explanations for why the regenerated bone in the sPG group was obviously superior to that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the signaling pathways related to cell adhesion, proliferation, and differentiation, such as JAK-STAT and Rap1 signaling pathways, were significantly activated, strongly supporting the idea that OIS plays a regulatory role on the viability and function of BMSCs. Meanwhile, mineralization and osteogenic differentiation-related genes (such as FGF1 , FGF23 , and BMP6 ) as well as their corresponding signaling pathways (such as MAPK and cytokine–cytokine receptor interaction) were significantly upregulated. Furthermore, angiogenesis-related genes (such as VEGFR1 and WNT5A ) as well as their corresponding signaling pathways (such as HIF-1) were significantly upregulated, which might be attributed to the addition of magnesium phosphate, zinc phosphate, and calcium silicate. In addition, ECM restructuring-related pathways (such as osteoclast differentiation) were also significantly activated, suggesting that OIS could regulate the structural remodeling of the regenerated bone. Although further experiments are required for in-depth confirmation, the results of this study imply that the regulatory roles of OIS on bone regeneration result from the synergistic action of various factors, including enhancing adhesion, proliferation, and differentiation, promoting mineralization and angiogenesis, and remodeling the ECM structure, which provided reasonable explanations for why the regenerated bone in the sPG group was obviously superior to that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The growth factor GDF-2 was positively associated with birth weight among female infants. GDF-2 is produced by the liver and maintains vascular quiescence, promotes osteogenesis, and is associated with improved glucose metabolism and insulin sensitivity [ 56 , 57 ]. GDF-2 has been suggested as a biomarker for cardiovascular disease since its levels are lower in individuals with essential hypertension and coronary heart disease compared with controls [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…With BMP-2-loaded collagen as the control, demineralized bone matrix was not capable of a 4 mm femur defect reconstruction, however, BMP-2 was able to achieve it [ 19 ]. Moreover, high BMP-2 doses could prevent bone overgrowth and ectopic bone formation in a negative feedback loop through the Wnt signaling pathway to guarantee the safety [ 43 ].…”
Section: Discussionmentioning
confidence: 99%